Impact of Antidepressant Fluoxetine on Female Fertility Using Zebrafish (Danio rerio) as an Experimental Model - Mothe, Teja; Mirza, Mehdi A.; Seethalakshmi, S (Aceh Journal of Animal Science, 2025)
Aquatic ecosystems are increasingly contaminated by pharmaceutical pollutants, including antidepressants such as fluoxetine, a selective serotonin reuptake inhibitor (SSRI). Detected in water-bodies, wastewater, and fish, fluoxetine poses potential risks to environmental and reproductive health. This study investigates the impact of fluoxetine exposure on zebrafish fertility, as SSRIs are known to influence reproductive function in humans. Five adult male-female zebrafish pairs were maintained in 10-litre tanks at 28C under a 14-hour light and 10-hour dark cycle and fed a high-protein diet thrice daily. To establish baseline fertility, each pair was initially spawned once, and the resulting eggs were discarded. The experiment was conducted over three cycles. In Cycle-1, pairs were separated for five days with daily water changes and allowed to spawn on Day-6. Total eggs and live eggs (clear and transparent) were recorded, with dead eggs (cloudy and opaque). In Cycle-2, both sexes were exposed to 3.2 g/L fluoxetine daily for five days before spawning. In Cycle-3, the same protocol as Cycle-1 was repeated without fluoxetine to observe delayed effects. Mean egg-counts were 231(14) in Cycle-1, 427(57) in Cycle-2, and 442(31) in Cycle-3. Significant difference (p0.05) between Cycle-1 vs Cycle-2 and Cycle-1 vs Cycle-3 was observed, while no significant difference was found between Cycle-2 and Cycle-3 (p0.05). Similarly, the proportion of live eggs declined across cycles: 47%(543/1155) in Cycle-1, 33%(704/2139) in Cycle-2, and 29%(641/2212) in Cycle-3. The decline was statistically significant between Cycle-1 vs Cycle-2 and Cycle-1 vs Cycle-3 (p0.05), but the difference between Cycle-2 and Cycle-3 was not significant (p0.05). A strong negative correlation was observed between total egg output and the proportion of live eggs. These findings suggest that fluoxetine enhances egg production while reducing egg viability. This underscores the reproductive toxicity of environmental fluoxetine exposure in aquatic species, with potential implications for human health. The study highlights pharmaceutical pollutions interconnected ecological and reproductive impacts.